Pengaruh berbagai dosis nutrisi terhadap pertumbuhan dan hasil tanaman selada (Lactuca sativa L) pada hidroponik sistem sumbu - Aaz Azamudin Tifani; Acep Atma Wijaya; Umar Dani; Asep Komala (Fakultas Pertanian Universitas Majalengka, 2023)
The experiment was carried out in the hydroponic hut Wa Adi, Gunungmanik Village, Talaga District, Majalengka Regency, West Java, with an altitude of 700 meters above sea level and a temperature of 20-26°C. The experiment was carried out from February to March 2022. The randomized block design (RBD) consisted of three treatments (t = 3 treatments) and was repeated ten times. Dosage factor (D) consists of three levels: d1 : 3 ml/liter (1.5 ml A + 1.5 ml B/liter), d2: 5 ml/liter (2.5 ml A + 2.5 ml B/liter), and d3: 7 ml/liter (3.5 ml A + 3.5 ml B/liter). Further tested using Duncan's Multiple Range Test at 5% level. Duncan's further test results showed that the administration of various doses of nutrients had a significant effect on plant height at 10 hst, plant height at 20 hst, plant height at 30 hst, number of leaves at 10 hst, number of leaves at 20 hst, leaf width at 20 hst, stover weight, and net weight. Each of the growth and yield components of lettuce plants treated with d2 (5 ml/liter) nutrient doses showed the best results compared to d1 (3 ml/liter) and d3 (7 ml/liter) nutrient doses.